FORMING RELIGIOUS BEHAVIOR OF GENERATION Z : HOW THE CONTRIBUTION OF HEREDITY - Dillah, Ibnu Ubay; Latipah, Eva; Nasar, Nasril (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Generation Z was born in 1997-2012, and now, the population in Indonesia has reached 68 million people. The characteristic of Generation Z is their high dependency on internet access every day. Seeing the phenomenon of Generation Z, which is thick with digital space, how does Generation Z carry out social interactions with the community, how is Generation Z's religious behavior, and whether heredity is a factor in the current phenomenon of Generation Z's religious behavior? The research used is a case study with qualitative research, data collection techniques used as observation, interviews, documentation, and online data tracking. The research subjects were students of the Z generation. The research objects have located in four universities in the Bantul area, the Special Region of Yogyakarta. The results showed that there was an influence of heredity on the behavior of Generation Z using Mendel's theory: 1) Segregation with a ratio of 1:2:1 and 2) Independent Assortment with a ratio of 9:3:3:1. In forming the religious behavior of Generation Z, the principles of religious moderation can be used: 1) Moderate Faith; 2) Moderate Worship; and 3) Moderate Morals.